(1 - 1/4 )x (1 - 1/4 )x (1 - 1/16 )x (1 - 1/25 )x (1 - 1/3 6)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1: =(x+y-3x)(x+y+3x)
=(-2x+y)(4x+y)
2: =(3x-1-4)(3x-1+4)
=(3x+3)(3x-5)
=3(x+1)(3x-5)
3: =(2x)^2-(x^2+1)^2
=-[(x^2+1)^2-(2x)^2]
=-(x^2+1-2x)(x^2+1+2x)
=-(x-1)^2(x+1)^2
4: =(2x+1+x-1)(2x+1-x+1)
=3x(x+2)
5: =[(x+1)^2-(x-1)^2][(x+1)^2+(x-1)^2]
=(2x^2+2)*4x
=8x(x^2+1)
6: =(5x-5y)^2-(4x+4y)^2
=(5x-5y-4x-4y)(5x-5y+4x+4y)
=(x-9y)(9x-y)
7: =(x^2+xy+y^2+xy)(x^2+xy-y^2-xy)
=(x^2+2xy+y^2)(x^2-y^2)
=(x+y)^3*(x-y)
8: =(x^2+4y^2-20-4xy+16)(x^2+4y^2-20+4xy-16)
=[(x-2y)^2-4][(x+2y)^2-36]
=(x-2y-2)(x-2y+2)(x+2y-6)(x+2y+6)
![](https://rs.olm.vn/images/avt/0.png?1311)
2n+1/n+1 có gt nguyên
<=>2n+2-1/n+1
2(n+1)-1/n+1
2-(1/n+1)
để 2n+1/n+1 có gt nguyên
<=>1/n+1 có gt nguyên
=>n+1 thuộc {+_1}
lm tiếp nhé
![](https://rs.olm.vn/images/avt/0.png?1311)
a) (5x+1) ^ 2 = 4^2 : 5^ 2
( 5x+1) ^2 = (4:5) ^2
=> (5x+1) = ( 4 : 5) = 0.8
5x = 0.8 - 1
x = 0.7 : 5
x = 0,14
![](https://rs.olm.vn/images/avt/0.png?1311)
b, 3/5 + 4/7 + 2/8 + 10/25 + 9/21 + 28/16
= 3/5 + 4/7 + 2/8 + 2/5 + 3/7 + 14/8
= (3/5 + 2/5) + ( 4/7 + 3/7) + ( 2/8 + 14/8)
= 1 + 1 + 7/4
= 2 + 7/4 = 15/4
c , 8/7 + 7/6 + 5/8 + 10/12 + 24/28 + 6/16
= c , 8/7 + 7/6 + 5/8 + 5/6 + 6/7 + 1/2
= (8/7 + 6/7) + (7/6 + 5/6) + 5/8 + 1/2
= 14/7 + 12/6 + 5/8 + 1/2
= 2 + 2 + 5/8 + 1/2
= 4 + 9/8 = 41/8
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1)x+\frac{5}{6}\times2\frac{2}{5}-1\frac{1}{4}=35\%\)
\(x+\frac{5}{6}\times\frac{12}{5}-\frac{5}{4}=\frac{7}{12}\)
\(x+\frac{5}{6}\times\frac{12}{5}=\frac{7}{12}+\frac{5}{4}\)
\(x+\frac{5}{6}.\frac{12}{5}=\frac{8}{5}\)
\(x+\frac{5}{6}=\frac{8}{5}:\frac{12}{5}\)
\(x+\frac{5}{6}=\frac{2}{3}\)
\(x=\frac{2}{3}-\frac{5}{6}\)
\(x=-\frac{1}{6}\)
HỌC TỐT !
\(2\)) \(\left|x-\frac{1}{2}\right|-\frac{3}{4}=0\)
\(\left|x-\frac{1}{2}\right|\) \(=0+\frac{3}{4}\)
\(\left|x-\frac{1}{2}\right|\) \(=\frac{3}{4}\)
\(x-\frac{1}{2}\) \(=\frac{3}{4}\)hoặc \(-\frac{3}{4}\)
Ta xét 2 trường hợp :
Trường hợp 1 : \(x-\frac{1}{2}=\frac{3}{4}\)
\(x\) \(=\frac{3}{4}+\frac{1}{2}\)
\(x\) \(=\frac{5}{4}\)
Trường hợp 2 : \(x-\frac{1}{2}=-\frac{3}{4}\)
\(x\) \(=-\frac{3}{4}+\frac{1}{2}\)
\(x\) \(=-\frac{1}{4}\)
Vậy \(x\in\text{{}\frac{5}{4};-\frac{1}{4}\)}
![](https://rs.olm.vn/images/avt/0.png?1311)
1
a) \(\left(3x+1\right)\left(3x-1\right)=9x^2-1\)
\(\left(x+5y\right)\left(x-5y\right)=x^2-25y\)
b) \(\left(x-3\right)\left(x^2+3x+9\right)=x^3-27\)
\(\left(x-5\right)\left(x^2+5x+25\right)=x^3-125\)
Bài 3:
a: \(\Leftrightarrow x^2+8x+16-x^2+1=16\)
=>8x+1=0
=>x=-1/8
b: \(\Leftrightarrow4x^2-4x+1+x^2+6x+9-5x^2+245=0\)
=>2x+255=0
=>x=-255/2
c: \(\Leftrightarrow x^3-6x^2+12x-8-x^3+64+6x^2+12x+6=49\)
=>24x+62=49
=>24x=-13
=>x=-13/24
d: =>x^3+8-x^3-2x=15
=>-2x=15-8=7
=>x=-7/2